SUDDEN DEATH CAUSED BY THORACIC AORTIC ANEURYSM RUPTURE (Journal of Forensic Medicine & Toxicology, 2025)
Sudden death can result from various causes. Thoracic aortic aneurysm rupture is rare and often silent until fatal. This case report highlights the importance of autopsy in identifying sudden cardiac deaths due to vascular causes.
Keywords: Sudden death; Cardiac tamponade; Thoracic aortic aneurysm